Analysis of overactive bladder symptoms after ceasing solifenacin treatment - Wlaźlak, Edyta; Suzin, Jacek; Dunicz-Sokołowska, Aldona; Bugaj, Andrzej Marcin; Surkont, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction: Nowadays there are neither detailed data nor guidelines concerning the recommended length of antimuscarinic treatment and the time of complaints recurring after ceasing the treatment. Overactive bladder is a chronic disease so probably constant treatment is needed. Non-invasive urodynamic studies in the form of a micturition diary are the basic way to confirm overactive bladder diagnosis, to evaluate the treatment efficacy of this disease and to perform the analysis of recurrence of complaints after ceasing the treatment. Aim of the study: The aim of the study was the evaluation of the recurrence of overactive bladder complaints after ceasing solifenacin treatment. Material and methods : The study included patients with overactive bladder complaints which were confirmed during non-invasive urodynamic studies (micturition diary) and were satisfied with the solifenacin (Vesicare, Astellas) treatment at a daily dose of 5 mg. After 6 months they decided by themselves to cease the treatment. Women were asked to come for a follow-up visit 3 and 6 months after the therapy was stopped. Results : Initially 37 women, aged 31-78 years (mean 62.8), were included into the analysis. At the visit after 3 months of treatment ceasing there were 34 patients, 8 patients fullfilled inclusion criteria for solifenacin treatment. At the visit after 6 months, among 23 women, 12 women fullfilled inclusion criteria of solifenacin treatment. There was observed a statistically significant enlargement in miction and urgency numbers 3 and 6 months after solifenacin ceasing. Conclusions : 6 months after ceasing solifenacin, recurrence of overactive bladder symptoms was observed in the most of patients, in whom this medicament was effective in clearing earlier occuring symptoms.